Carreira e comprometimento organizacional: ampliando a sua compreensão - Cantarelli, Neiva Maria (2017)
This study was developed to verify the relation between the categories of career anchors and the dimensions of organizational commitment, considering the reality of education clerks of a federal college, located in the center of Rio Grande do Sul state. A descriptive research with quantitative character was conducted for this study. The questionnaire had its structure based on two models: Inventory of Career Anchors (SCHEIN, 1993, 1996) and the Basis of Organizational Commitment Scale (MEDEIROS et al., 2005) and was applied to 655 education clerks, who occupy positions of classification levels C, D and E of the career plan. Regarding the categories of career anchors, the results obtained show Will of Serving and Dedication to a Cause, Lifestyle, and Security and Stability, in this order, as predominant, since the three of them have inherent features of the civil service. The anchor of General Administrative Career was the least valorized, which shows the feeble interest of the clerks in assuming the kind of attributions expected on their effective position. Regarding the dimensions of organizational commitment, the results show a normative commitment, through the valorization of Obligation through Development Basis. Moreover, the results show a low valorization of the normative basis, Obligation of Staying. On the interpretation of the results obtained, it was used factors measurement, through valuables weight, on which it was verified that the values indicate commitment above the average on the Affection and Obligation through Development. These results can be considered positive because they show that the clerks identify themselves to the values and goals of the institution and are conscious of the necessity of struggling to achieve these goals. When the relation between the themes is established, it is possible to affirm that the results show very low correlations, in most cases. The results give evidence of low correlations and no moderate correlation. The low correlations happened between the Affective Organizational Commitment Basis and the Career Anchor Will of Serving / Dedication to a Cause, and also between commitment basis Lack of Alternatives and the anchor Security and Stability.